Quality of life impact of public policies for energy and telecommunications. - Engi, D.
The objective of this preliminary investigation is to identify actual current public policy options for managing these two interdependent infrastructures to explore possible impacts on measures of quality of life. Causal relationships are investigated between public policies and quality of life related to two critical infrastructures energy and telecommunications. Specific components of these infrastructures are selected to narrow the scope of the investigation. Within the broad area of energy, the focus is the electric power industry. The telephone and Internet communications subsystems are the focus within the telecommunications infrastructure. For the purposes of this work, these two subsystems are referred to as the telecommunications infrastructure, even though a more encompassing definition would typically include broadcast television and radio, enterprise networks, amateur radio systems, and a variety of other voice and data exchange systems.
Keywords: Internet communications subsystems; Causal loop diagrams; Causal relationships; Electric power industry; Interdependent infrastructures; Model architecture; Public policies; Quality of life impact; Security challenges; Telephone communications subsystems